Comparison of weather station and climate reanalysis data for modelling temperature-related mortality - Mistry, Malcolm N; Schneider, Rochelle; Masselot, Pierre; Royé, Dominic; Armstrong, Ben; Kyselý, Jan; Orru, Hans; Sera, Francesco; Tong, Shilu; Lavigne, Éric; Urban, Aleš; Madureira, Joana; et al. (Scientific reports, 2022)
Epidemiological analyses of health risks associated with non-optimal temperature are traditionally based on ground observations from weather stations that offer limited spatial and temporal coverage. Climate reanalysis represents an alternative option that provide complete spatio-temporal exposure coverage, and yet are to be systematically explored for their suitability in assessing temperature-related health risks at a global scale. Here we provide the first comprehensive analysis over multiple regions to assess the suitability of the most recent generation of reanalysis datasets for health impact assessments and evaluate their comparative performance against traditional station-based data. Our findings show that reanalysis temperature from the last ERA5 products generally compare well to station observations, with similar non-optimal temperature-related risk estimates. However, the analysis offers some indication of lower performance in tropical regions, with a likely underestimation of heat-related excess mortality. Reanalysis data represent a valid alternative source of exposure variables in epidemiological analyses of temperature-related risk.
Keywords: vysoká teplota; Temperature; podnebí; teplota; Climate; Weather; počasí; Hot Temperature